Adsorption, self-assembly and self-metalation of tetra-cyanophenyl porphyrins on semiconducting CoO(100) films - Ammon, Maximilian; Raabgrund, Andreas; Schneider, M. Alexander (Surface Science, 2022)
The adsorption properties of free base 5,10,15,20-tetrakis(p-cyanophenyl)porphyrin (2H-TCNPP) on thin films of rock salt (rs) CoO(100) on Au(111) was studied in ultra-high vacuum (UHV) by a combination of low-temperature scanning tunneling microscopy and spectroscopy (STM/STS) and density functional theory (DFT). Films of rs-CoO(100) on Au(111) are prepared with excellent quality in a suitable thickness range. Particularly, we found that films of only 1 nm thickness show a semiconducting energy gap of Eg=(2.5±0.2)eV. Upon deposition at 300 K, 2H-TCNPP adsorbs flat-lying and self-assembles in a long-range ordered superstructure that is stable at 80 K. The adsorption geometry of the molecules on the surface and within the self-assembly is analyzed by DFT. We find that the self-assemblies are stabilized by hydrogen bridge bonding via the functional cyano groups. Our STS data shows molecular states within the fundamental gap of the CoO. By comparison with the calculated DOS we determine the energetic positions of the frontier orbitals and find that the first three LUMO states 2H-TCNPP are located within the band gap, whereas the HOMO is shifted 1 eV below the CoO conduction band edge. Upon annealing to 420 K the molecules change their appearance in STM images and a new prominent electronic state located at the center of the molecule is formed. We interpret this changed configuration as Co-TCNPP created by self-metalation on the oxide surface.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Cobalt oxide; Electronic states; Pophyrin; Scanning tunneling microscopy; Self-assembly; Self-metalation